2016
DOI: 10.3899/jrheum.150613
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Safety of Baricitinib in Japanese Patients with Active Rheumatoid Arthritis Receiving Background Methotrexate Therapy: A 12-week, Double-blind, Randomized Placebo-controlled Study

Abstract: Objective.To evaluate efficacy and safety, baricitinib [Janus kinase (JAK) 1/JAK2 inhibitor] was compared with placebo in Japanese patients with active rheumatoid arthritis (RA) despite background treatment with methotrexate (MTX).Methods.This was a phase IIB, double-blind, randomized, placebo-controlled study (clinicaltrials.gov: NCT01469013). Patients had moderate to severe active adult-onset RA despite stable treatment with MTX. Patients (n = 145) were randomized in a 2:1:1:1:1 ratio to placebo or 1 mg, 2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
95
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 27 publications
9
95
0
3
Order By: Relevance
“…The safety and tolerability profile of baricitinib through the 104-week OLE period of this phase IIb study was generally consistent with prior observations gathered during shorter durations of exposure 3,4,5 . Few patients experienced AE leading to discontinuation, and AE rates including infection stabilized or diminished with prolonged treatment.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The safety and tolerability profile of baricitinib through the 104-week OLE period of this phase IIb study was generally consistent with prior observations gathered during shorter durations of exposure 3,4,5 . Few patients experienced AE leading to discontinuation, and AE rates including infection stabilized or diminished with prolonged treatment.…”
Section: Discussionsupporting
confidence: 74%
“…In a phase IIa study in patients with active RA despite treatment with disease-modifying antirheumatic drugs (DMARD), baricitinib [4, 7, or 10 mg administered once daily (QD)] improved the signs and symptoms of RA after 12 weeks of treatment compared to placebo, with no unacceptable safety findings 3 . In a phase IIb double-blind study conducted in Japanese patients, QD baricitinib was also associated with significant improvement in RA disease activity compared to placebo at the primary 12-week timepoint 4 . In a larger, phase IIb, double-blind, randomized, placebo-controlled, dose-ranging study in patients with active RA despite treatment with methotrexate (MTX) ± other conventional synthetic DMARD, significantly more patients in the…”
mentioning
confidence: 99%
“…With regard to other efficacy measures in the four phase 3 studies, results obtained from Japanese subpopulations were also generally similar to those of overall study population. In all four of the phase 3 studies, the safety and tolerability profile of baricitinib in Japanese patients appeared acceptable and generally consistent with results from the prior phase 2 study of baricitinib in Japan [17], and with the overall study population data [18][19][20][21]. In study RA-BEGIN, the incidence of TEAEs during 52 weeks was 97% of the Japanese patients in the baricitinib 4-mg monotherapy group, and 92% in the baricitinib þ methotrexate group versus 83% in the methotrexate monotherapy group, compared to 71, 78 and 72%, respectively, in the overall study population.…”
Section: Discussionsupporting
confidence: 70%
“…In this study, 4-mg and 8-mg baricitinib showed earlier and/or greater improvements in most measures of disease activity than the 1-mg and 2-mg doses over 12 weeks of treatment when compared with placebo [17]. Baricitinib was well-tolerated in this study; the safety profile of 4-mg appeared to offer some advantages over the 8-mg dose, and was similar to that of the lower doses.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation